The consequences of price differentiation for regional development in Poland - Przekota, Grzegorz (Progress in Economic Sciences; No 4 (2017): Progress in Economic SciencesDO - 10.14595/PES/04/010, 2017)
Each region in Poland has a different economic potential due to its own specific features. Taking account of the specific nature of individual regions is important for the management of the country as a whole and of its particular regions. Existing disparities in the economic development may lead to many negative phenomena, such as internal migration or regional marginalization. Excessive price and income inequalities may weaken economic growth throughout the country. It is important for the coherence of the whole country that the disparities between regions are not too big. The study determines the consequences of price differentiation for regional development in Poland. The analysis was conducted using the coefficient of variation, correlation coefficient, regression coefficient and medium pace. The regions differ in terms of development, dynamic growth and wages. However, prices are much less diverse.